An Application of Semi-empirical Physical Model of Tsunami-Bore Pressure on Buildings - Kihara, Naoto; Kaida, Hideki (Frontiers in Built Environment, 2019)
Characteristic patterns of tsunami wave pressure on buildings is divided into three types, depending on its vertical profiles and time, which is observed after the tsunami impacted the buildings. The first one is the impulsive pressure, which is observed just after the tsunami impacted the buildings. The second one is the bore pressure, which is observed after the impulsive pressures. The third one is the quasi-steady pressure, which is observed after the bores go away from the buildings. In this study, based on characteristics of bore pressure observed in a hydraulic experiment, a semi-empirical physical model of bore pressure is developed by applying a turbulent bore theory. Also, we present an application method of the semi-empirical physical model to evaluations of bore pressure with usage of numerical results of inundation simulations of two-dimensional nonlinear shallow water equation models. Furthermore, we apply the semi-empirical physical model to evaluations of pressure acting on buildings in an inundation area by carrying out numerical simulations of tsunami inundation.